Muscle metabolic stress determines cancer cachexia severity in mice - Alves, Christiano; Goodyear, Laurie; Brum, Patricia (Frontiers in Physiology, 2022)
Objectives: To determine the metabolic effects of cancer-conditioned media on myotube metabolism and to understand whether the variability of these effects is associated with cancer cachexia progression. Materials and Methods: We established single-cell clones from murine Lewis lung carcinoma (LLC) cells and generated conditioned media from each clonal line. Differentiated primary mouse myotubes were incubated with conditioned media derived from each individual clonal cell line. After initial analysis, we selected a specific LLC clonal cell line that failed to induce metabolic stress in myotubes for further investigation in vitro and in vivo. Results: Short-term incubation with conditioned media from 10/34 LLC clonal cells failed to affect oxygen consumption rate (OCR) in myotubes. Incubation with parental LLC-conditioned media decreased protein content and changed the expression of key regulators of muscle function in myotubes, but the incubation of conditioned media from a selected clone that failed to affect OCR in myotubes also did not affect protein content and expression of muscle regulators. Mice injected with parental LLC cells had significantly reduced body mass and muscle wasting compared to the mice injected with cells derived from this selected LLC clone. Conclusions: Factors secreted by LLC cells induce metabolic stress in primary myotubes and induce cancer cachexia in mice. However, a selected clonal LLC cell line that failed to induce metabolic stress in myotubes also promoted weaker catabolism in mice. These novel findings establish that early disruption of muscle oxidative metabolism is associated with cancer cachexia progression.